Free radical scavenging activity of aqueous and alcoholic extracts of Glycyrrhiza glabra Linn. measured by ferric reducing antioxidant power (FRAP), ABTS bleaching assay (αTEAC), DPPH assay and peroxyl radical antioxidant assay - Gupta, Mradu; Karmakar, Nandita; Sasmal, Saswati; Chowdhury, Saikat; Biswas, Suman (International Journal of Pharmacology and Toxicology, 2016)
The present study evaluates the in vitro antioxidant free radical scavenging capacities of aqueous and alcoholic extracts of Glycyrrhiza glabra since this medicinal plant has been traditionally used in Ayurvedic system of medicine as a tonic, rejuvenator, demulcent and expectorant. Total phenolic content of alcoholic extract and aqueous extract was found as 18.70 and 23.26 Gallic acid equivalents/mg while the total flavonoid content was assessed as 15.03 and 6.62 Quercetin equivalents/mg respectively. IC50 (µg/ml) of alcoholic, aqueous extract and Ascorbic acid was found to be 65.064±3.538, 73.423±9.057 and 18.156±1.356 in Hydrogen Peroxide Radical Scavenging, 1.424±0.013, 1.632±0.052 and 0.879±0.273 in DPPH radical scavenging, and 335.948±29.040, 251.891±6.330 and 6.142±0.061 during FRAP essay. Similarly, during ABTS radical scavenging, IC50 (µg/ml) was assessed as 575±26.694, 683.9±49.220 and 6.337±0.167 for alcoholic, aqueous extract and Trolox respectively. While both the extracts showed substantial and significant free radical scavenging activity during the study which is compared to that of standard drug, the alcoholic extract of Glycyrrhiza glabra exhibits higher in vitro antioxidant activity than the aqueous extract in all assessment methods except FRAP, possibly due to higher concentrations of flavonoids in it, validating and confirming the therapeutic properties ascribed to it in Ayurvedic texts.